2019
DOI: 10.1186/s13014-019-1227-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel stereotactic body radiation therapy (SBRT)-based partial tumor irradiation targeting hypoxic segment of bulky tumors (SBRT-PATHY): improvement of the radiotherapy outcome by exploiting the bystander and abscopal effects

Abstract: BackgroundDespite the advances in oncology, patients with bulky tumors have worse prognosis and often receive only palliative treatments. Bulky disease represents an important challenging obstacle for all currently available radical treatment options including conventional radiotherapy. The purpose of this study was to assess a retrospective outcome on the use of a newly developed unconventional stereotactic body radiation therapy (SBRT) for PArtial Tumor irradiation of unresectable bulky tumors targeting excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 41 publications
(40 reference statements)
1
76
0
1
Order By: Relevance
“…Our preclinical findings indicated that the hypoxic in respect to normoxic tumor cells, if selectively irradiated as inductor of BE/AE, show higher potential for the generation of BE/AE [3]. The subsequent translation of these findings to a clinic led to the introduction of a novel SBRT-based PArtial Tumor irradiation targeting HYpoxic clonogenic cells (SBRT-PATHY) showing promising BE/AE-response rates [2,4]. Recently, the Italian group confirmed efficacy of SBRT-PATHY in their initial experience [5].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our preclinical findings indicated that the hypoxic in respect to normoxic tumor cells, if selectively irradiated as inductor of BE/AE, show higher potential for the generation of BE/AE [3]. The subsequent translation of these findings to a clinic led to the introduction of a novel SBRT-based PArtial Tumor irradiation targeting HYpoxic clonogenic cells (SBRT-PATHY) showing promising BE/AE-response rates [2,4]. Recently, the Italian group confirmed efficacy of SBRT-PATHY in their initial experience [5].…”
Section: Introductionmentioning
confidence: 79%
“…The median follow-up was 11.8 months (range: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. At the time of analysis, one patient (treated at "most favourable" time-position) had died 22 months after SBRT-PATHY because of causes other than cancer.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the preclinical finding that irradiating the hypoxic fraction of the tumor may intentionally induce non targeted effects, they proposed a new irradiation technique that consists of stereotactic body radiotherapy for partial irradiation of bulky tumors (larger than 6 cm), targeting exclusively their central hypoxic segment (SBRT-PATHY) with high dose (10 Gy). With SBRT-PATHY, they recently observed impressive results in a small retrospective clinical series with local and abscopal response rate of more than 90 and 50%, respectively [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Tubin and colleagues used VMAT to deliver 1-3 fractions each of 10-12 Gy of SBRT-PATHY in lesions of more than 6 cm, with the aim of keeping the dose within the peritumoral tissue as low as reasonably achievable. The dose was prescribed to the 70% isodose-line, however there is no particular mention that this prescription method has been chosen to reduce the dose to the tumor periphery [2,3].…”
Section: Introductionmentioning
confidence: 99%